Research on the social integration and depression risk of middle-aged and older adults with multiple chronic conditions in China - Deng, Weijian; Yang, Simin; Ouyang, Xin; Jiang, Tao; Zhu, Junmin; Yang, Feng (Frontiers in Public Health, 2025)
ObjectiveThe aging of the global population is intensifying, and the issue of depression among middle-aged and older individuals in China has garnered significant attention. Social integration is considered closely related to the risk of depression in patients with multiple chronic conditions (MCCs). This study aims to explore the relationship between different dimensions of social integration and depression in middle-aged and older individuals.MethodsThis study utilized data from the 2018 China Health and Retirement Longitudinal Study (CHARLS), including 2,901 middle-aged and older individuals with MCCs. Depression risk was assessed using a depression scale. Social integration was measured across three dimensions: economic integration, relational integration, and community integration. Statistical analyses were conducted using Logit and Tobit models to explore the relationship between social integration and depression among middle-aged and older individuals.ResultsThere was no significant association between overall social integration and the risk of depression, but economic integration and community integration were negatively correlated with the risk of depression, and relational integration was positively correlated with the risk of depression, and this relationship was heterogeneous among different demographic characteristics. Sensitivity analysis and subgroup analysis further confirmed the robustness of the results.ConclusionMental health interventions for middle-aged and older adults MCCs patients should consider the multi-dimensional characteristics of social integration. It is recommended to improve the economic status of the middle-aged and older adults, improve the quality of family and social interactions, and pay attention to the construction of the community environment. And further explore the interaction of each dimension and its applicability in different contexts.